A evolução do conhecimento acerca da hemoterapia durante a formação médica - Fabiana Chagas Camargos Piassi (2017)
The appropriate use of blood products requires large knowledge in Transfusion Medicine. While the importance of continuing medical education is well-defined, the characteristics and the scope of Transfusion Medicine education during undergraduate is unknown. Studies using questionnaires to identify learning gaps and to guide educational interventions have concluded that doctors' knowledge about transfusion is scarce. The objective of this study was to evaluate the performance in Transfusion Medicine of undergraduate students and residents of different specialties of the Clinical Hospital of UFMG and to identify the variables concerning attitudes associated with learning. KAP questionnaire (knowledge, attitude and practice) was developed, validated and applied between 77 medical students of the last year and 65 residents from clinics with the highest number of transfusion prescriptions. Physicians and residents of Hematology and Transfusion Medicine were considered specialists in the subject, with a total of 18 professionals. The questionnaire included theoretical questions about Transfusion Medicine, as well as the resolution of clinical cases as a strategy to evaluate the transfusion practice. Key topics of relevance to general practitioners were included in questionnaire. Questions about attitudes in the face of transfusion practice was measured by a 5-point Likert scale. To validate the questionnaire, the Content Validity Coefficient (CVC) was calculated from the score given by five specialists in Transfusion Medicine in relation to the pertinence of the topics and clarity of the language of each question. Pre-test was performed to evaluate the understanding of the questions and the response time. The questionnaire was applied during classes or scientific meetings. Students (35.0%) and residents (49.5%) had low percentage of correct answers. Among the specialists, the result was 74.9%. Both in theoretical issues and in clinical cases, the performance of the specialists was higher than residents, who in turn was above the students. In group analysis, the students performed better on the theoretical questions, but among the resident there was no difference of results between the groups of questions. The specialists performed better in clinical cases. Regarding attitudes, when compared to students, residents said that they felt confident in transfusion prescribing, as well as in patients counseling about the risks and benefits of the procedure, and attributed lesser importance to the graduation on the current knowledge of Transfusion Medicine. The attitude variables that impacted in students' performance was to have participated in the indication of a blood transfusion throughout the graduation (p = 0.022), being the largest number of participations the variable of greater significance (p = 0.003). The students that attributed major importance of the graduation course to the current knowledge of Transfusion Medicine had better performance (p = 0.011). It can then be concluded that the questionnaire was valid for the evaluation of the acquisition of competences in Transfusion Medicine, in that it adequately differentiated specialists, residents and students of the 6th year of Medicine. Scarce knowledge about transfusion processes is related to insufficient basic training in Transfusion Medicine not only during undergraduate courses, but also in medical residency, and the repetition of practice has confirmed its relevance for acquiring skills in this area. The performance in resolution of the clinical cases were related to a transfusion practice, which justifies its use as a teaching and learning strategy.